Promoting students’ critical thinking through online learning in higher education: Challenges and strategies - Tathahira, Tathahira (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Living in the millennial era has encouraged all the learners to one step ahead maximizing the existed and updated technology for learning. Maintaining autonomous and long-distanced learning should have been introduced and implemented in higher education. Involving in an online learning environment is not enough without the ability to think critically. Critical thinking is the ability that is essentially required for learners in a higher education context. This paper discusses the challenges and strategies for implementing learners’ critical thinking through online learning. This paper used the literature study approach, in which all the information in this paper was obtained from books and journal articles. Briefly, the findings reveal that online learning can be good support for students to improve their critical thinking ability. However, there are also several challenges to do so involving the socio-cultural matter, the students’ previous learning habits, and the familiarity of using updated technology for learning. To end the discussion, the author provides several strategies to overcome those challenges. The well-designed online discussion (interactivity), critical-thinking learning content, and well-maintained instructions are several factors needed by online course instructors in order to improve their students’ critical thinking.